The Role of Internal Memory to Enhance The Vocabulary By Using Word Wall - Sandi; Ali Wira Rahman (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2018)
This research is based on the students’ problem regards English especially on vocabulary. Vocabulary is the important thing for students in the process of acquiring, learning, mastering, and using the language they learn. Without having vocabulary nothing can be convey. Mastering vocabulary will help the students to communicate easier with other people. Those reason become some of the considerations of the researcher to conduct a research when doing an observation at SMK Bahari Parepare because the students showed their limited of vocabulary. Then, modifying the method could be the problem solving for the limited vocabulary. in this case, the implementation of word wall as an media was suggested to overcome the problem. Finally, this research was intended to reveal that: can the role of internal memory by using word wall improve the vocabulary of the eleventh grade students of SMK Bahari Parepare significantly. This research used quasi experimental method, with two group pre-test and post-test design. The population was the eleventh grade students of SMK Bahari Parepare. The samples were drawn by using random sampling technique that consisted of 45 students which were class XI Teknika A as experimental class and class XI Nautika as control class. The data were acquired by using vocabulary test. The vocabulary mastery test was applied in the pre-test and post-test. The data required from vocabulary test was analyzed by using ttest and percentage technique. The result of the data analysis showed that the students’ vocabulary mastery improved significantly. It was showed by the mean score of the pretest was (56.19) and the post-test was (76.904). It showed that word wall can improve vocabulary of the eleventh grade students of SMK Bahari Parepare significantly. Besides, the mean score of the students in post-test (76.904) was higher than the standard scoring Departemen Pendidikan Nasional Republik Indonesia (70.00). After analyzing the data by using the t-test formula, the result of t-test value in post-test was (2.147) and t-table value was (2.021). Those indicated that H1 was accepted and H0 was rejected. It meant that word wall can improve vocabulary of the eleventh grade students of SMK Bahari Parepare significantly.